LIMONENE QUANTIFICATION BY GAS CHROMATOGRAPHY WITH MASS SPECTROMETRY (GC-MS) AND ITS EFFECTS ON HYDROGEN AND VOLATILE FATTY ACIDS PRODUCTION IN ANAEROBIC REACTORS - Camargo, Franciele Pereira; Sarti, Arnaldo [UNESP]; Alecio, Alberto Camilo [UNESP]; Sabatini, Carolina Aparecida; Tallarico Adorno, Maria Angela; Silveira Duarte, Iolanda Cristina; Amancio Varesche, Maria Bernadete (Soc Brasileira Quimica, 2020)
The inhibition effect of limonene on the organisms involved in anaerobic reactors may affect obtaining H-2 in this process. Rapid and precise limonene quantification is desirable to characterize wastewaters. The objective of this research was to develop a Gas Chromatography Coupled to Mass Spectrometry (GC-MS) method to determine limonene concentration in liquid samples from batch reactors applied to H-2 production at 30 degrees C. Method validation was carried out through calibration curves (3 to 20 mg L-1 of limonene), in addition to evaluating its precision (CV = 0.1%). linearity (R-2 = 0.979), limits of detection (1.7 mg L-1) and quantification (4.2 mg L-1). Its inhibitory effect was evaluated with increasing concentrations of limonene (without addition to 2000 mg L-1). Limonene affected the starting time of H-2 production (lambda), since lambda was 8.7 h in control assays and 15 h with 2000 mg L-1 of limonene. The same was observed for obtaining H-2, since 19.5 mmol H2 L-1 was obtained in control assays and 8.7 mmol H2L-1 was obtained in assays with 2000 mg L-1 of limonene. This method was effective for limonene determination in liquid samples from batch reactors and could be used for characterization and control of anaerobic reactors.
Keywords: wastewater; sewage sludge; anaerobic digestion; hydrogen; volatile fatty acids; limonene